Emerging New Delhi metallo-β-lactamase-1-type-producing Gram-negative bacteria isolated from Cairo University Pediatric Hospital, Cairo, Egypt. (December 2016) - Wassef, Mona; Abdelhaleim, Mona; Ghaith, Doaa; El-Mahdy, Yasmin
Highlights: Prevalence of bla NDM-1-type gene among Gram-negative bacteria was 24% by real-time PCR. ICUs are deemed to be the epicentre and the main source of development and amplification of antimicrobial resistance. Strict infection control measures are mandatory to contain the spread of NDM-1 outbreaks. Abstract: New Delhi metallo-β-lactamase (NDM) compromises the efficacy of almost all β-lactam antibiotics, including carbapenems. This study aimed to screen for the bla NDM-1-type gene and NDM-1-type carbapenemase production among Gram-negative bacteria in Cairo University Pediatric Hospital (Cairo, Egypt). Among 382 Gram-negative clinical isolates collected over the period October 2013 to May 2014, 100 clinical isolates showing reduced carbapenem (imipenem and meropenem) susceptibility were included in this study. Initial phenotypic screening for NDM enzyme production was performed by Etest for metallo-β-lactamases (EMBL). Genotypic detection of the bla NDM-1-type gene was done by Taq Man real-time PCR. Metallo-β-lactamase production was detected in 23% of the isolates by EMBL, whereas 24% of the isolates were found to be positive for the bla NDM-1-type gene by real-time PCR. The EMBL sensitivity was 79.2%, specificity was 94.7%, positive predictive value was 82.6%, negative predictive value was 93.5% and overall accuracy was 91.0%. Seventeen (70.8%) of bla NDM-1-type -positive cases were hospital-acquired in origin, whilst 7 cases (29.2%) were community-acquired. Eleven isolates (45.8%) harbouring bla NDM-1-type were found in critical care units. In conclusion, the high prevalence of bla NDM-1-type carbapenemase gene among Gram-negative bacteria, with its great potential for spread in intensive care units, warrants the attention of a nationwide surveillance programme to contain its spread.